Divergent responses of different endothelial cell types to infection with Candida albicans and Staphylococcus aureus. - Kati Seidl; Norma V Solis; Arnold S Bayer; Wessam Abdel Hady; Steven Ellison; Meredith C Klashman; Yan Q Xiong; Scott G Filler (PLoS ONE, 2012)
Endothelial cells are important in the pathogenesis of bloodstream infections caused by Candida albicans and Staphylococcus aureus. Numerous investigations have used human umbilical vein endothelial cells (HUVECs) to study microbial-endothelial cell interactions in vitro. However, the use of HUVECs requires a constant supply of umbilical cords, and there are significant donor-to-donor variations in these endothelial cells. The use of an immortalized endothelial cell line would obviate such difficulties. One candidate in this regard is HMEC-1, an immortalized human dermal microvascular endothelial cell line. To determine if HMEC-1 cells are suitable for studying the interactions of C. albicans and S. aureus with endothelial cells in vitro, we compared the interactions of these organisms with HMEC-1 cells and HUVECs. We found that wild-type C. albicans had significantly reduced adherence to and invasion of HMEC-1 cells as compared to HUVECs. Although wild-type S. aureus adhered to and invaded HMEC-1 cells similarly to HUVECs, an agr mutant strain had significantly reduced invasion of HMEC-1 cells, but not HUVECs. Furthermore, HMEC-1 cells were less susceptible to damage induced by C. albicans, but more susceptible to damage caused by S. aureus. In addition, HMEC-1 cells secreted very little IL-8 in response to infection with either organism, whereas infection of HUVECs induced substantial IL-8 secretion. This weak IL-8 response was likely due to the anatomic site from which HMEC-1 cells were obtained because infection of primary human dermal microvascular endothelial cells with C. albicans and S. aureus also induced little increase in IL-8 production above basal levels. Thus, C. albicans and S. aureus interact with HMEC-1 cells in a substantially different manner than with HUVECs, and data obtained with one type of endothelial cell cannot necessarily be extrapolated to other types.